SYNTHESIS OF MOLECULAR IMPRINTED POLYMER SALBUTAMOL USING METHACRYLIC ACID MONOMER AND TRIMETHYL PROPANE TRIMETHACRYLATE (TRIM) AS A CROSS-LINKER THROUGH SUSPENSION POLYMERIZATION - SUSANTI, IKE; SAFITRI, NISA; PRATIWI, RIMADANI; HASANAH, ALIYA NUR (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aims to determine the analytical performances and characteristics of MIP salbutamol made with methacrylic acid (MAA) monomer and trimethylpropane trimethacrylate (TRIM) cross-linker through suspension polymerization. Methods: The MIP salbutamol was synthesized using suspension polymerization. The analytical performances of MIP, such as the adsorption ability, adsorption capacity and selectivity, were evaluated by Spectrophotometer UV-Vis. The physical characterization of MIP and NIP were evaluated using FTIR, TEM-EDS, Brunauer-Emmett-Teller (BET) method and Barret-Joyner-Halenda (BJH) method. Results: Molecular Imprinted Polymer (MIP) showed better analytical performance than Non-Imprinted Polymer (NIP), the adsorption ability of MIP and NIP reached about 90.43% and 53.92%, respectively. The MIP was selective for salbutamol when compared to terbutaline and salmeterol xinafoate with an imprinting factor (IF) of 1.2841. The MIP has spherical shape particles with diameters in the range of 10-100 µm with a surface area of 185.546 m2/g, pore volume of 0.257 cm3/g, and pore size of 16.599 Å. Conclusion: The Based on these results, MIP salbutamol, has the potential to be developed as a method for the preparation of salbutamol analysis from biological samples.